Indigenous Food Yam Cultivation and Livelihood Practices in Cross River State, Nigeria: Implications for Community-Based Food Tourism Education 126 - Maxwell-Borjor Achuk Eba (Indonesian Journal of Educational Studies, 2025)
This study examines indigenous yam cultivation practices in the Obudu community of Cross River State, Nigeria, and their implications for community-based food tourism education. Using a mixed-methods approach, the study finds that over 90% of farmers depend on indigenous knowledge for seasonal adjustment, storage, and fertility enhancement. Nearly 70% of yam producers are aged 60 years and above, and farmers respond to weak public support through informal networking and local associations. Yam cultivation is deeply embedded in socio-cultural beliefs and rituals, shaping livelihood networks and community resilience. The study argues that these indigenous practices represent an underutilized resource for community-based food tourism education. Integrating indigenous knowledge into educational programming can promote cultural preservation, economic empowerment, and sustainable agricultural development. The findings have implications for tourism policy, agricultural extension, and community development in Cross River State and similar contexts. Keywords: indigenous knowledge, yam cultivation, community-based tourism, food tourism education, Cross River State.